2014
DOI: 10.1016/j.ijsu.2014.08.393
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient repair for inguinal hernia in elderly patients: Still a challenge?

Abstract: Elective inguinal hernia repair in the elderly has a good outcome, and age alone should not be a drawback to day case treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…The mortality rate was zero in all three intervention groups as no deaths were reported. Only one study had mortality as a primary outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality rate was zero in all three intervention groups as no deaths were reported. Only one study had mortality as a primary outcome.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 46 studies reported mortality within 90 days. The studies covered 10 332 patients: 7976 had LA, 722 regional anaesthesia and 1634 GA. Methods of follow‐up included clinical examination, telephone call, questionnaire , contact with family doctor and electronic patient data management. Six studies did not report methods of follow‐up.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with an age ≤18 years, ASA score III-IV, BMI ≤15 or >40, hepatic failure, acute kidney injury or chronic renal failure, heart failure, reported allergy to local anesthetics, congenital or acquired bleeding disorders were considered not eligible for the surgical and the anesthesiological procedure. Patients with an age ≥75 years were not excluded from the study, because, even if they could have worse general health status and higher ASA scores than the younger patients, the surgical morbidity results to be not significantly different [13].…”
Section: Methodsmentioning
confidence: 99%
“…Today, for example, surgeons routinely perform elective laparoscopic cholecystectomy, inguinal hernia repair, and partial mastectomy in an outpatient setting. 1 3 At many institutions, surgeons commonly perform parathyroidectomy and thyroid lobectomy as day-surgery procedures requiring only a short period of observation in the recovery room, and some surgeons are even applying this management paradigm to total thyroidectomy. 4 Indeed, many high-volume surgeons are performing thyroidectomy in an outpatient setting (same-day surgery) as the rule rather than the exception.…”
Section: Introductionmentioning
confidence: 99%